The Just War and Jihad: Violence in Judaism, Christianity, and Islam By R. Joseph Hoffman, ed. (New York: Prometheus Books, 2006. 303 pages.) (American Journal of Islam and Society, 2007)
The fifteen chapters of this book bring together scholars from a variety offields to examine and analyze what they perceive to be a relationshipbetween religion and violence. Generating a feeling of déjà vu, they rehashpreviously developed assumptions, arguments, and biases that tend to ignoreunderlying causes related to the “existence of the sacred,” for reasons apparentlybeyond the domain of secular comprehension. The articles reiterateconventional secular arguments about the dangers of religious convictionson “peace” and tend to vary in quality and consistency, which reflects on thebook’s overall merit.Although it is not feasible to go into each chapter’s details, it is importantto underscore their basic thrust and common theme: the issue of legitimationand what confers legitimacy on action, be it violent in nature, such asin war or conflict, or simply legal and organizational. Hector Avalos (chapter6) puts it candidly. In the “relative” framework of “empirico-rationalism,”he argues that religious violence is always “immoral,” positing that “life,” asa manifestation of that which “exists,” is worth more than that which does notexist (p. 113). However, this does not preclude war in the absolute. Onearrives at this conclusion after reading J. Harold Ellens’ “The Obscenity ofWar” (chapter 2) as well as the Committee for the Scientific Examination ofReligion’s (CSER) “Protocol on Religion, Warfare, and Violence” (chapter 15) ...